Correlation Between Ophthalmologic and Neuroradiologic Findings in Type 1 Neurofibromatosis. Issue 1 (March 2022) - Godinho, Gonçalo; Esteves-Leandro, João; Alves, Gonçalo; Madeira, Carolina; Faria, Olinda; Brandão, Elisete; Magalhães, Augusto; Falcão-Reis, Fernando; Penas, Susana
Abstract : Background: Neurofibromatosis Type 1 (NF-1) is a genetic disease affecting the eye, and ocular findings such as Lisch nodules (LN) or optic pathway gliomas (OPGs) are a part of its diagnostic criteria. Recent imaging technologies such as infrared (IR) imaging and optical coherence tomography (OCT) have highlighted the visualization of choroidal focal abnormalities in these patients, even in the absence of other ocular lesions. This study aimed to establish a morphological multimodal evaluation of choroidal findings in patients with NF-1, correlating them with central nervous system (CNS) findings. Methods: This retrospective study included 44 eyes from 22 patients with NF-1. Central 30° IR imaging was obtained, and the number and total area of detectable lesions were calculated. Both macular and optic disc scanning with OCT were performed, with and without the enhanced depth imaging technique, to assess the presence of choroidal focal hyperreflective lesions. Central macular thickness, ganglion cell layer, and outer nuclear layer thickness were assessed, as well as subfoveal choroidal thickness. The peripapillary retinal nerve fiber layer (RNFL) thickness was also assessed. Patients' magnetic resonance images (MRI) were reviewed and categorized by a neuroradiology specialist, determining the presence of OPGs and CNS hamartomas. Correlations between the ophthalmological and neuroradiological findings were established. Results: Patients' mean age was 16.4 ± 7.3 years and 59.1% were women. On the MRI, 86.4% of the patients had CNS hamartomas, and 34.1% of the eyes had OPGs. LN were described in 29.5% of the eyes, whereas a total of 63.4% of the eyes presented the characteristic hyperreflective lesions in IR imaging, all of them matching the underlying choroidal lesions. A mean of 2.9 ± 3.3 lesions per eye and a median total lesion area of 1.52 mm 2 were found. The presence of OPGs was correlated with a greater number ( P = 0.004) and a larger area ( P = 0.006) of IR lesions. For a cut-off of 3.5 lesions per eye, the sensitivity and specificity for the presence of OPGs were 75% and 80%, respectively. For a total lesion area of 2.77 mm 2, the sensitivity and specificity for the presence of OPGs were 69.2% and 93.1%, respectively. Eyes with OPGs presented a significant reduction in the temporal RNFL ( P = 0.018) thickness, as well as a reduction in subfoveal choroid thickness ( P = 0.04). No relations were found between CNS hamartomas and ophthalmological findings. Conclusions: This study suggests that focal choroidal abnormalities are correlated with the presence of CNS lesions as OPGs in patients with NF-1, and it might be a surrogate for the need for CNS imaging in these patients.